Implementation of Ghana’s Standards-Based Physical Education Curriculum for Primary Schools: Classroom Teachers’ Perspectives - Sofo, Seidu; Seibu , Munkaila; Thompson , Emmanuel (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. In Ghana, generalist classroom teachers are responsible for teaching physical education (PE) in primary schools. This study examined Ghanaian classroom teachers’ perspectives on the implementation of Ghana’s standards-based PE curriculum. Materials and methods. This study utilized a convergent mixed methods design. The Physical Education Curriculum Questionnaire (PECQ) and semi-structured interviews served as the primary data sources. Teachers’ likelihood of meeting the requirement to teach the PE lesson (RTPE) twice a week (30 minutes per period) or once a week (60 minutes per period) served as the response variable. The predictor variables included: teacher knowledge, support, resources, policy, teacher education, professional development, and demographic factors. Participants were 1432 public primary school classroom teachers (39.53% male and 60.47% female) from 14 regions of Ghana. Thirty-four semi-structured interviews were conducted. Results. The results indicated that 21.4% of participants taught PE as required, 9.7% teachers did not teach PE during the school year. Only 47.42% of teachers reported familiarity with the PE curriculum. Slightly over one-third indicated that their teacher education programs adequately prepared them to teach the primary PE content. Additionally, 60.41% of the classroom teachers reported that trained physical education specialists, rather than classroom generalists, should be responsible for teaching PE in primary schools. A fitted binary logistic regression showed that teacher knowledge, the number of years teaching current class, teacher education (training), teaching experience, sex, resources, region, policy, and certification were significant predictors of RTPE. The qualitative data identified seven themes: non-teaching of PE, teacher knowledge, curriculum relevance, teacher education, lack of support, lack of monitoring and supervision, and continuous professional development. Conclusions. School physical education can play an active role in preventing physical activity-related diseases. The study highlights the need for policymakers to redefine the PE curriculum to align with the nation’s social and cultural contexts.